(untitled) (Indonesian Tax Justice Review, 2024)
Despite their appearance of neutrality, tax systems often produce gender-differentiated outcomes. This paper examines Indonesia’s tax policy framework from a gender and tax justice perspective. Using qualitative policy analysis, the study assesses personal income tax, value-added tax, and social contribution schemes to identify implicit gender biases. The findings reveal that consumption-based taxes disproportionately affect women, particularly those engaged in informal and unpaid care work. This paper contributes to the global tax justice literature by emphasizing the importance of integrating gender-responsive approaches into tax design. Indonesia’s case provides empirical evidence from a developing country context, reinforcing calls for inclusive fiscal policies that address structural gender inequalities. The study advances global discussions on equitable taxation by demonstrating how gender analysis enhances the normative foundations of tax justice.